Defining Shock and Preshock for Mortality Risk Stratification in Cardiac Intensive Care Unit Patients. (January 2021) - Jentzer, Jacob C.; Burstein, Barry; Van Diepen, Sean; Murphy, Joseph; Holmes, David R.; Bell, Malcolm R.; Barsness, Gregory W.; Henry, Timothy D.; Menon, Venu; Rihal, Charanjit S.; Naidu, Srihari S.; Baran, David A.
Abstract : Background: Previous studies have defined preshock as isolated hypotension or isolated hypoperfusion, whereas shock has been variably defined as hypoperfusion with or without hypotension. We aimed to evaluate the mortality risk associated with hypotension and hypoperfusion at the time of admission in a cardiac intensive care unit population. Methods: We analyzed Mayo Clinic cardiac intensive care unit patients admitted between 2007 and 2015. Hypotension was defined as systolic blood pressure <90 mm Hg or mean arterial pressure <60 mm Hg, and hypoperfusion as admission lactate >2 mmol/L, oliguria, or rising creatinine. Associations between hypotension and hypoperfusion with hospital mortality were estimated using multivariable logistic regression. Results: Among 10 004 patients with a median age of 69 years, 43.1% had acute coronary syndrome, and 46.1% had heart failure. Isolated hypotension was present in 16.7%, isolated hypoperfusion in 15.3%, and 8.7% had both hypotension and hypoperfusion. Stepwise increases in hospital mortality were observed with hypotension and hypoperfusion compared with neither hypotension nor hypoperfusion (3.3%; all P <0.001): isolated hypotension, 9.3% (adjusted odds ratio, 1.7 [95% CI, 1.4–2.2]); isolated hypoperfusion, 17.2% (adjusted odds ratio, 2.3 [95% CI, 1.9–3.0]); both hypotension and hypoperfusion, 33.8% (adjusted odds ratio, 2.8 [95% CI, 2.1–3.6]). Adjusted hospital mortality in patients with isolated hypoperfusion was higher than in patients with isolated hypotension ( P =0.02) and not significant different from patients with both hypotension and hypoperfusion ( P =0.18). Conclusions: Hypotension and hypoperfusion are both associated with increased mortality in cardiac intensive care unit patients. Hospital mortality is higher with isolated hypoperfusion or concomitant hypotension and hypoperfusion (classic shock). We contend that preshock should refer to isolated hypotension without hypoperfusion, while patients with hypoperfusion can be considered to have shock, irrespective of blood pressure. Abstract : Supplemental Digital Content is available in the text.